2018
DOI: 10.1002/ijc.31802
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive drugs and prostate cancer survival after radical prostatectomy in Finland—A nationwide cohort study

Abstract: Antihypertensive (anti-HT) drugs targeting renin-angiotensin-aldosterone (RAA)- system have been associated with improved prostate cancer (PCa)-specific survival. Challenge is that often multiple drugs are used simultaneously. We evaluated the association between use of anti-HT drugs and PCa survival among 14,422 surgically treated Finnish PCa patients. Information on drug purchases was obtained from a national prescription database. We used Cox regression to calculate hazard ratios (HRs) and 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 19 publications
6
28
2
Order By: Relevance
“…Recently, a cohort study conducted by Santala et al . published in the International Journal of Cancer reported the association between prostate cancer survival after radical prostatectomy and antihypertensive drug use . We are interested in their findings that calcium channel blockers use before prostate cancer diagnosis was not significantly associated with the risk of prostate cancer death (multivariable adjusted hazard ratio = 0.84, 95% confidence interval = 0.51–1.40).…”
Section: Association Between Prostate Cancer and Calcium Channel Blocmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, a cohort study conducted by Santala et al . published in the International Journal of Cancer reported the association between prostate cancer survival after radical prostatectomy and antihypertensive drug use . We are interested in their findings that calcium channel blockers use before prostate cancer diagnosis was not significantly associated with the risk of prostate cancer death (multivariable adjusted hazard ratio = 0.84, 95% confidence interval = 0.51–1.40).…”
Section: Association Between Prostate Cancer and Calcium Channel Blocmentioning
confidence: 77%
“…1 Recently, a cohort study conducted by Santala et al published in the International Journal of Cancer reported the association between prostate cancer survival after radical prostatectomy and antihypertensive drug use. 2 We are interested in their findings that calcium channel blockers use before prostate cancer diagnosis was not significantly associated with the risk of prostate cancer death (multivariable adjusted hazard ratio = 0.84, 95% confidence interval = 0.51-1.40). However, a case-control study conducted by Rotshild et al revealed that a positive association was detected between the risk of prostate cancer and calcium channel blockers use (odds ratio = 1.10, 95% confidence interval = 1.02-1.18).…”
mentioning
confidence: 99%
“…Consistently, silencing of MR resulted in enhanced resistance to enzalutamide and AR activity [55]. Moreover, the effects of diverse antihypertensive medication on prostate cancer survival following radical prostatectomy were tested in the Finnish population, and overall, the antihypertensive treatment was associated with increased death risk [56]. These findings clearly establish the importance of AR and MR cross talk and complex ligand interactions in prostate cancer, which could be further studied in other cancers and cancer subtypes where AR signaling can play a role.…”
Section: Prostate Cancermentioning
confidence: 91%
“…We are very pleased to answer the comments on our manuscript "Antihypertensive drugs and prostate cancer survival after radical prostatectomy in Finlanda nationwide cohort study." 1 Lai et al wonder whether androgens would be a potent confounding subject for prostate cancer (PCa) diagnosis. At first, it is important to consider that risk factors for PCa diagnosis might be different compared to risk factors for PCa death, as may also confounding subjects be.…”
Section: Dear Editormentioning
confidence: 99%
“…We are very pleased to answer the comments on our manuscript “Antihypertensive drugs and prostate cancer survival after radical prostatectomy in Finland – a nationwide cohort study.”…”
mentioning
confidence: 99%